Towards the 3rd Architectural Digital Turn (EAAE Annual Conference Proceedings, 2023)
We introduce the BioDigital platform as the third Digital Turn, enabled by the incorporation of “BioElectrical Systems” (BES) into urban contexts (PHOENIX, 2022). Using metabolically generated electricity produced by microbial biofilms, BES are accessible by directly visualizing their electrical transactions on a screen (the BioDigital interface) and are characterized by three pedagogical and technological principles: i) (up to 12V) power generation, ii) (microbial) information and iii) biochemical transformation. Integrating life-flows between microbes (comprising the metabolic base of the biosphere), big (environmental) data governed by AI, electrochemistry and human inhabitation, this transactional platform is fundamentally environmental turning organic waste into electricity, cleaned water, bioremediation services, bodily monitoring, and biosynthesis.